1997
DOI: 10.1212/wnl.49.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Cat-scratch encephalopathy

Abstract: We present a case of cat-scratch disease in a 9-year-old girl, complicated by encephalopathy and seizures. Bartonella (formerly Rochalimaea) henselae is the causative agent in cat-scratch disease; methods now available for detection of this pleomorphic, gram-negative bacterium, including polymerase chain reaction amplification and indirect fluorescence antibody testing, may lead to changes in standard criteria used to verify a diagnosis of cat-scratch disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 5 publications
2
23
0
1
Order By: Relevance
“…CIDP is an autoimmune process in which both humoral and cellular factors are thought to participate in the pathogenesis. Wheeler et al also suggested an immune response as a pathophysiological mechanism responsible for CSD encephalopathy 1. In our patient a delayed myelin destruction is induced by sensitised macrophages, originally activated by the Bartonella infection.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…CIDP is an autoimmune process in which both humoral and cellular factors are thought to participate in the pathogenesis. Wheeler et al also suggested an immune response as a pathophysiological mechanism responsible for CSD encephalopathy 1. In our patient a delayed myelin destruction is induced by sensitised macrophages, originally activated by the Bartonella infection.…”
supporting
confidence: 59%
“…However, neurological complications associated with CSD are rare, with encephalopathy being by far the most common form (90%) of nervous system involvement. Encephalopathy occurs in 2%–3% of patients and is more common in adults than in children with the onset varying from a few days to months after diagnosis of CSD 1. Other known neurological manifestations, often in combination with encephalopathy, are neuroretinitis, oculoglandular disease of Parinaud, myelopathy, radiculopathy or abducens nerve, and facial nerve paresis.…”
mentioning
confidence: 99%
“…5 Infection of the central nervous system (CNS) with B. henselae is uncommon and typically presents with an encephalopathy and seizures. [6][7][8][9] In a study of 1200 cases of CSD there was neurological involvement in only 2% of cases, with encephalopathy being the most common complication. 3 In a series of 76 patients with CSD and neurological complications, 80% had an encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…II νόσος των αμυχών της γάτας αποτελεί το συχνότερο αίτιο μονήρους λεμφαδενοπάΟειας σε νεαρά άτομα με εξαίρεση επιχώριες λεμφαδενίτιδες λόγω εμφανών τοπικών φλεγμονών. Σε ασθενείς με ανοσοκαταστολή έχει αναφερθεί εξάπλωση του βακτηρίου και εντόπιση του στο ήπαρ και το σπλήνα (Slater et al 1990, Noah et al 1995, Wheeler et al 1997, Spach et al 1998, Margileth 2000, Roux et al 2000, Fournieretal. 2001, Koehler et al 2003, Eremeeva et al 2007, Florin et al 2008, Chomel et al 2009, Dietrich et al 2010.…”
Section: θεραπευτικη αντιμετωπισηunclassified